La fortuna del 'Secolo d'Oro' Per Marco Lombardi - Innocenti, Barbara (Moderna/Comparata, 2018)
The 17th century was the "century of theatre" for Europe, due to the quantity and the quality of dramatic works and to the great number of scenic inventions. Studying this century with focus on France and Spain, in light of the interpenetration between Classicism, Mannerism and Baroque, means discussing and deepening some key themes which are essential not only to the knowledge of a historical and literary era, but to modernity itself. Thanks to the participation of well-known specialists, who have read exemplary texts within the overall history of theatre and a rich iconography, this volume edited by Barbara Innocenti (who also transcribed an original document on the death of Louis XIV found in the archives of Pistoia) offers the required comparative attitude. The insights on great authors (mainly Molière, Tirso de Molina, the 'Tasso effect' in French literature...) favour comparisons and intersections which make it possible to outline a horizon of "European" culture, enriched by a creative dialogue with the contemporary on the translation and staging level. Therefore, the "Golden Century" goes beyond its own borders, crossing times, geographic areas and literatures.